Elevated levels of IL-12/IL-23p40 in Nova Scotia Duck Tolling Retrievers with autoimmune disease and lymphoma - Malin Nilsson; Sergey V. Kozyrev; Sara Saellström; Siri Johansson; Göran Andersson; Kerstin Lindblad-Toh; Helene Hansson-Hamlin; Henrik Rönnberg (Scientific Reports, 2024)
Abstract The Nova Scotia Duck Tolling Retriever (NSDTR) is predisposed to immune mediated rheumatic disease (IMRD), steroid-responsive meningitis-arteritis (SRMA) and certain forms of cancer. Cytokines are the main regulators of the immune system. Interleukin 2 is a cytokine involved in activation of T regulatory cells, playing a role in central tolerance and tumor immunity. Interleukin 12 and interleukin 23 share the same subunit, p40, and are both pro-inflammatory cytokines. The aim of this study was to compare levels of IL-2 in healthy NSDTRs to those with cancer or autoimmune disease and to compare levels of IL-12/IL-23p40 in healthy NSDTRs and beagles versus NSDTRs with cancer or autoimmune disease. 62 dogs were included in the analysis of IL-12/IL-23p40; healthy NSDTRs (n = 16), healthy beagles (n = 16), NSDTRs autoimmune (n = 18) and NDSTRs lymphoma/mastocytoma (n = 12) and 68 dogs for IL-2; healthy (n = 20), autoimmune (n = 36) and lymphoma/mastocytoma/adenocarcinoma (n = 12). NSDTRs with autoimmune disease had higher levels of IL-12/IL-23p40 compared to healthy dogs (p = 0.008). NSDTRs with lymphoma also had higher levels of IL-12/IL-23p40 compared to healthy NSDTRs (p = 0.002). There was no difference in levels of IL-2 between healthy and diseased NSDTR. Statistical analysis was performed using Bonferroni corrections for multiple testing. These findings can contribute to the knowledge of autoimmune disease and cancer in dogs.